What kind of hominin first left Africa? - Scardia, Giancarlo [UNESP]; Neves, Walter A.; Tattersall, Ian; Blumrich, Lukas (Wiley, 2020)
Recent discoveries of stone tools from Jordan (2.5 Ma) and China (2.1 Ma) document hominin presence in Asia at the beginning of the Pleistocene, well before the conventional Dmanisi datum at 1.8 Ma. Although no fossil hominins documenting this earliest Out of Africa phase have been found, on chronological grounds a pre-Homo erectus hominin must be considered the most likely maker of those artifacts. If so, this sheds new light on at least two disputed subjects in paleoanthropology, namely the remarkable variation among the five Dmanisi skulls, and the ancestry of Homo floresiensis.
Keywords: early Pleistocene; Homo floresiensis; Homo georgicus; Out of Africa